2014
DOI: 10.1111/ped.12295
|View full text |Cite
|
Sign up to set email alerts
|

Wilms tumor: Experience of a hospital in southern Brazil

Abstract: Death is closely related to late diagnosis in WT. Oncologic services should also be concerned about morbidity caused by therapeutic options in cases of late diagnosis, and the consequences for quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
(102 reference statements)
4
6
1
Order By: Relevance
“…Of significance in this study is the 73.7% survival among those who completed the available treatment, viz., surgery and prescribed chemotherapy. Though this figure is less than the reported >90% among patients who completed standard treatment from more developed countries and some developing countries, it may be due to the lack of radiotherapy treatment and high proportion of anaplasia in our cases. Also, 83% survival of our cases with stage 2 disease, where the need for complex supportive care is minimal, may compare with the global result.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Of significance in this study is the 73.7% survival among those who completed the available treatment, viz., surgery and prescribed chemotherapy. Though this figure is less than the reported >90% among patients who completed standard treatment from more developed countries and some developing countries, it may be due to the lack of radiotherapy treatment and high proportion of anaplasia in our cases. Also, 83% survival of our cases with stage 2 disease, where the need for complex supportive care is minimal, may compare with the global result.…”
Section: Discussioncontrasting
confidence: 75%
“…This is evidenced by the long duration of symptoms before presentation, absence of stage 1 disease in all of our series, and more than 80% of our cases with advanced disease at presentation. Though similar delayed presentation has been reported in some other developing countries, it contrasts sharply with the situation in more developed countries where most patients have early disease at presentation . Late presentation is associated with complications of the disease, and coupled with the coexisting morbidities in our setting will require more intensive care, which unfortunately is also lacking.…”
Section: Discussionsupporting
confidence: 54%
“…Though the included studies did not indicate the reason for this, it may be related to the health‐seeking behavior of the region and the reported improvement of access to health care, which might encourage the patients to present earlier 30 . Despite this, with the pooled data the proportion of cases with advanced disease, average size of tumors, and the cases with anaplasia may be similar to the findings from other LMICs, 36–38 but they are still higher than the figures from HICs and the global benchmark 1,34,40,41 . Persisting large proportion of advanced disease at presentation, large tumor weight, and anaplasia cases may be due to the lingering challenge of delayed presentation of most cases in Africa 1–3,7,13 as well as the reported tendency of African WT to express markers of adverse clinical behavior and treatment resistance 42 …”
Section: Discussionmentioning
confidence: 79%
“…Current evidence indicates that this WT success is commonly associated with HICs where studies have shown a significant reduction of the barriers to WT management in the last century 1,2,34,35 . This contrasts nonetheless with the finding of poorer outcome in many low‐ and middle‐income countries (LMICs) in Africa 2,3,7–9,15,20–22 and outside of Africa 1,4,36–38 due to some persistent patient‐related, socioeconomic, and institutional factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation